(untitled) (CIPEEX, 2025)
Deep vein thrombosis (DVT) is a serious condition associated with complications such as pulmonary embolism, which significantly impact morbidity and mortality. Despite advances in diagnosis and prophylactic strategies, the early identification of risk factors remains essential to improving clinical outcomes. This integrative review aimed to identify and critically analyze the main risk factors for DVT in adults, with an emphasis on the hospital setting. The study used the PICo strategy (P: adults; I: risk factors; Co: hospital setting). Searches were conducted in PubMed, SciELO, and Scopus databases, using the descriptors “trombose venosa profunda,” “deep vein thrombosis,” “fatores de risco,” and “risk factors,” combined with Boolean operators. A total of 152 articles were initially identified, of which 47 duplicates and 89 that did not meet eligibility criteria were excluded. Sixteen articles were assessed in full, and eight original studies published in the last five years, in Portuguese or English, with free full-text availability, were included in the final analysis. The most frequent risk factors were advanced age, prolonged immobilization, previous history of DVT, comorbidities such as diabetes and hypertension, and elevated levels of the laboratory marker D-dimer, which is a sensitive indicator of thrombosis. In orthopedic and critically ill patients, hospital-related factors such as central venous catheter use, prolonged surgical time, and mechanical ventilation showed statistically significant associations. Obesity demonstrated variable impact, probably related to methodological heterogeneity among studies, whereas patients with COVID-19 presented an increased risk due to systemic inflammation and corticosteroid use. The heterogeneity of the findings highlights the need for individualized risk stratification, combining clinical and laboratory information to enhance the prevention and management of DVT. The implementation of protocols based on this stratification may reduce thromboembolic complications and optimize hospital resources. These findings reinforce the importance of individualized approaches and contribute to the development of evidence-based practices in hospital care. Future multicenter studies with larger samples are needed to validate these findings and consolidate clinical guidelines.